Kajian Terhadap Kompleks Kobalt, Nikel Dan Kupram Dengan Salisaldehida Tiosemikarbazon - Manaf, Hasimah Abdul (Universiti Sains Malaysia, 1985)
Salicylaldehyde thiosemicarbazone has been 'little used as an analytical reagent for the determination of metals. In this project SAT is used for determination of cobalt, nickel and copper by spectrophotometric. A study also covers the potential of salicylaldehyde thioseaicarbazone as an analytical separating agent through complexation with cobalt, nickel and copper.